2018
DOI: 10.1126/science.aar2866
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission from subplate neurons controls radial migration of neocortical neurons

Abstract: The neocortex exhibits a six-layered structure that is formed by radial migration of excitatory neurons, for which the multipolar-to-bipolar transition of immature migrating multipolar neurons is required. Here, we report that subplate neurons, one of the first neuron types born in the neocortex, manage the multipolar-to-bipolar transition of migrating neurons. By histochemical, imaging, and microarray analyses on the mouse embryonic cortex, we found that subplate neurons extend neurites toward the ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 21 publications
1
110
0
Order By: Relevance
“…The rodent subplate layer contains a diverse population of cells, containing both pallium derived projection neurons (TBR1+, presumed glutamatergic) and ganglionic eminence derived interneurons (GABAergic; Hevner & Zecevic, ). Moreover, it is one of several compartments in which ganglionic eminence derived interneurons migrate tangentially during cortical development (Parnavelas, ) and recently subplate has been implicated in regulating radial migration (Ohtaka‐Maruyama et al, ). We have previously used microarray profiling of the mouse subplate layer at E15, E18 and P8 with the aim of identifying different cell types within the subplate (Hoerder‐Suabedissen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The rodent subplate layer contains a diverse population of cells, containing both pallium derived projection neurons (TBR1+, presumed glutamatergic) and ganglionic eminence derived interneurons (GABAergic; Hevner & Zecevic, ). Moreover, it is one of several compartments in which ganglionic eminence derived interneurons migrate tangentially during cortical development (Parnavelas, ) and recently subplate has been implicated in regulating radial migration (Ohtaka‐Maruyama et al, ). We have previously used microarray profiling of the mouse subplate layer at E15, E18 and P8 with the aim of identifying different cell types within the subplate (Hoerder‐Suabedissen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This region was observed in the Flt1-tdsRed neocortex and in the wild-type (WT) neocortex, and our immunostaining with Pax6 further revealed APs within this zone ( Figure 1G, asterisk). In contrast, vessels in the embryonic CP were oriented vertically (Figures 1A,1B,and 1D,arrows; Figure S1B), with the subplate (SP) forming the boundary (Ohtaka-Maruyama et al, 2018) between these vertically oriented vessels and the honeycomb-patterned vascular plexus in VZ/SVZ/IZ ( Figure 1B, open arrowheads).…”
Section: Regularity Of Angiogenesis During Neocortical Developmentmentioning
confidence: 99%
“…To determine whether E10 pallial-born neurons migrate ventrally, we used in utero electroporation (IUE), which is useful for labeling neurons that contribute to SP 5 (Shimogori and Ogawa, 2008;Ohtaka-Maruyama et al, 2018). Live monitoring (at E11 or E12) of flat-mount cerebral walls (Figures 2A and 2B, Video S1A) and coronal slices ( Figures 2C and 2D, Videos S1B and S1C) prepared following IUE at E10 revealed that heavily IUE-labeled cells constituted PP and underwent a massive ventral migration.…”
Section: Neurons Born In the Dorsal Pallium At E10 Including Presumpmentioning
confidence: 99%
“…In addition to their previously known roles in layer formation (Ogawa et al, 1995;Ohtaka-Maruyama et al, 2018) and the connection between the cortex and thalamus Ghosh et al, 1990;reviewed in Allendoerfer and Shatz, 1994;Hoerder-Suabedissen and Molnár, 2015), PP neurons promote, through their ventral streaming via tangential migration (E11-12) and axon-based traction (E13), the 1 4 ventral extension of CP (E14), thereby playing a priming physical role in postnatal neocortical arealization. A recent study by Barber et al (2015) showed that appropriate and balanced tangential migration of CR cells from three different origins (i.e., the hem, septum, and PS angle) to cooperatively cover the entire pallial surface by E12 underlies the normal regionalization of postnatal neocortex.…”
Section: Experimental Weakening Of the Pp Stream Dorsally Shifts The mentioning
confidence: 99%
See 1 more Smart Citation